Metsänkäsittelyn vaikutus lähteiden vedenlaatuun ja pienilmastoon - Koukka, Silja (2024)
Boreal springs are valuable habitats in boreal forests, where the biodiversity can be much higher than in surrounding forest. Still, their ecological status has been decreasing significantly due to human activities, like forest management. Inadequate buffer zones have been found to result in degradation of the microclimate and water quality of other small water bodies, such as streams, but this has not been studied with springs. Therefore, in this MSc Thesis the impact of forest management, logging and ditching, on the water quality and microclimate of boreal springs was studied using data collected from 18 springs. Linear models were used to investigate the relationships between spring variables and the forest management at the surrounding and landscape level. The results showed that the stable microclimate characteristics of the spring become more unstable, with increasing maximum temperatures and decreasing minimum humidities along a narrowing buffer zone. Increases in temperature, electrical conductivity and total nitrogen concentration were observed in the spring water, as well as a decrease in pH with the increase in recent clear-cuts around the spring. In addition, the total phosphorus concentration of the water decreased as the width of the buffer zone increased, and the dissolved organic carbon content decreased with increasing tree basal area. Drainage was not found to affect the water quality of the springs, but this was explained by the structure of the study sites. The study provides strong evidence that adequate buffer zones are essential especially for the microclimate of the spring. Even though the relationship between water quality impairment and forest management has some uncertainties, the results suggest the degrading effect of clear-cutting on spring water quality. An inadequate buffer zone cannot protect the spring from environmental changes, such as extreme temperatures and nutrient spikes caused by clear-cutting, which can lead to the loss of sensitive spring specialist species adapted to stable conditions.